Multistage tower performance for a desalinator controlled by eletric energy - Felipe Alves Albuquerque AraÃjo (2016)
Solar desalination plants are used for water treatment using solar radiation as an energy source, but its incidence varies, either in terms of time, the weather, the seasons or the presence of clouds. These factors complicate the understanding of the process variables influence and constructive geometric parameters. In this work, the experimental results, obtained by operation with a thermal desalination unit with heat recovery, are presented. The process occurs by controlled heating, by electricity flowing through a resistance present at the base of desalination tower (storage tank). In addition to the tank, the tower also comprises stages, consisting of polyurethane profiles, to prevent heat loss to the external environment, and aluminum trays in W format, through which flows the water generated by the steam condensation from the next lower stage. On the sides of each stage profiles, there are condensate collection gutters connected to hoses that lead the produced fluid to collection canisters. The production of desalinated water, with the use of a hydrophobic film on the bottom of the aluminum trays, where the condensate drains, was evaluated. Also biological, physical and chemical, chromatographic and spectrometric tests were conducted in order to verify the quality of the water produced. The best desalinator operating condition of the study, with the maximum output gain ratio (GOR) for the system of 7.92, was obtained with a potential difference of 120V, 600W power and five stages in the desalination tower. The film did not increase the water production, but it was also not observed contamination of water samples by the hydrophobic product.